The Effect of Length of Residence and Geographical Origin on the Social Inclusion of Immigrants - Mario Millán-Franco (Psychosocial Intervention, 2019)

(untitled)
This study analysed the effect of length of residence and place of origin on the social inclusion of immigrants. Social support, resilience, sense of community, and satisfaction with life were used as indicators of social inclusion. Previous studies on social inclusion of immigrants were predominantly of static nature. A synthetic cohort design that examines temporal effects in distinct cohorts was used to analyse the effect of time on levels of social inclusion. It was hypothesised that place of origin would moderate the positive effect of length of residence. The study was conducted in Málaga (Spain). The participants consisted of 2,374 immigrants from Africa (597), East Europe (565), Latin America (652), and Asia (560). The results suggest that length of residence has a positive effect on social inclusion and that shorter cultural distance facilitates the process of social inclusion, especially among Latin American immigrants. However, the moderating effects of place of origin only reached statistical significance for satisfaction with life. A multidimensional and dynamic approach is needed to fully understand the process involved in the social inclusion of immigrants. This is based on the assumption that the positive effect of length of residence is not linear in the short term but manifests over the long term.